2015
DOI: 10.1021/jacs.5b03618
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-Directed Chromism of Phthalein Dyes

Abstract: Phthalein dyes in the quinone dianion form (pseudo-D3, colored) are transformed into the lactone dianion form (pseudo-T(d), colorless) through encapsulation in a T(d)-symmetric host even under basic conditions (pH ∼10). The compatibility in size and symmetry between the lactone and the cavity is essential to the transformation. Upon addition of a guest that strongly binds to the cavity, the encapsulated phenolphthalein is expelled, the color of the basic solution is regained, and the host-guest complexation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…This can be explained by the very low concentration of the saturated solution of 6 in water, which implies that the equilibrium concentration of the unoccupied cage, [ 4 ], remains relatively high even for a high value of K assoc ( K assoc = [ 6 ⊂ 4 ]/[ 4 ]·[ 6 ]). Overall, these results indicate that the energy penalty associated with distorting the cage can be overcome by the favorable host–guest interaction energy, and that by preferentially binding an otherwise unstable isomer of the guest, the cage can render this isomer the stable one (as has also been observed by Fujita and co-workers 40 for free vs. encapsulated phthalein dyes).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This can be explained by the very low concentration of the saturated solution of 6 in water, which implies that the equilibrium concentration of the unoccupied cage, [ 4 ], remains relatively high even for a high value of K assoc ( K assoc = [ 6 ⊂ 4 ]/[ 4 ]·[ 6 ]). Overall, these results indicate that the energy penalty associated with distorting the cage can be overcome by the favorable host–guest interaction energy, and that by preferentially binding an otherwise unstable isomer of the guest, the cage can render this isomer the stable one (as has also been observed by Fujita and co-workers 40 for free vs. encapsulated phthalein dyes).…”
Section: Resultssupporting
confidence: 73%
“…We showed that the encapsulation of different spiropyrans in a hydrophobic cavity of the cage was accompanied by spontaneous switching to an otherwise unstable, colored isomer, highlighting the cage’s capacity to revert the relative stability of different isomers of the same molecule. 40 The encapsulated spiropyrans remained photoswitchable and could be converted to the colorless form upon irradiation with blue light. These findings constitute an unprecedented case of negative photochromism of spiropyran in a hydrophobic environment (here, the cavity of the cage).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cavity of cage I was exploited to induce chromism in phthalein dye. 93 As the shape and size of molecules affect their encapsulation in the host, tetrahedral lactone can ideally fit into the cavity of cage I, and hence is encapsulated and stabilized in the cavity more than quinone. This led to disappearance of the pink color due to shifting of the equilibrium towards lactonization.…”
Section: L 4 Octahedral Msccs (Cage I)mentioning
confidence: 99%
“…In the past decades, metal coordination‐driven self‐assembly has been proven to be a highly efficient strategy for producing predesigned 2D and 3D architectures . The ingenious ligand design and the meticulous choice of metal ions make the assemblies feature well‐defined geometry and cavity, which have potential applications in the fields such as guest binding, catalysis, and molecular machines . However, these rigid metallosupramolecules have relatively poor solubility, which therefore limits their utilization.…”
Section: Methodsmentioning
confidence: 99%